PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X PADA MATA PELAJARAN BIOLOGI DI MAS AL WASHLIYAH SERBELAWAN - Aprilia Pratiwi, Devi; Lihardo Hulu, Irwan; Saragih, Marlindoaman (Jurnal Metabio, 2023)
This study is a classroom action research study aimed to describe the improvement of students' critical thinking skills in Biology through the implementation of the Think Talk Write learning model. The subjects were 40 students of class X MIPA-1 MAS Al Washliyah Serbelawan. The study was conducted through four stages: planning, implementation, observation, and reflection. This classroom action research study used a collaborative model that prioritizes cooperation between teachers and researchers. Data collection methods included observation and a critical thinking test. The instruments used were teacher and student observation sheets and a 20-item critical thinking test. Before being used as a data collection tool, the instruments were pre-tested to determine validity, reliability, and normality. Based on the results, the average improvement in students' critical thinking skills was 50% in cycle I, then increased to 92.5% in cycle II. From these results, it can be concluded that the implementation of the Think Talk Write learning model can improve students' critical thinking skills in class X MIPA-1 MAS Al Washliyah Serbelawan.